The Effect of Emotion Regulation on Post-Traumatic Stress Disorder among Student Victims of Sexual Harassment: The Mediating Role of Self-Esteem - Eko Sujadi; Bukhari Ahmad (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Sexual harassment is a global problem that often affects female students both inside and outside the campus environment. Sexually aware victims can be at risk of experiencing post-traumatic stress disorder (PTSD). This study aims to investigate the influence of emotional regulation and self-esteem on PTSD, and analyze the role of self-esteem in mediating the relationship between the two. Researchers used an online cross-sectional design to reduce face-to-face meetings with respondents. The population of this study consisted of undergraduate students from various universities in Indonesia. The sampling technique used quota sampling, so that 1,439 students were obtained. However, only 170 people who said they had been victims came forward. Researchers adapted three research scales, namely the PTSD CheckList - Civilian Version (PCL-C), the Emotion Regulation Difficulties Scale: The DERS-16, and the Rosenberg Self-Esteem Scale. The data analysis technique uses Partial Least Squares Structural Equation Modeling (PLS-SEM). Research findings prove that emotional regulation and self-esteem have a significant influence on PTSD in open victims. In addition, self-esteem provides a mediating effect between the relationship between emotion regulation and PTSD. The latest information in this research has implications for preventing and handling cases of sexual disclosure on campus. University leaders need to make special regulations regarding open cases. Apart from that, there is a need for programmed guidance and counseling services for students who are victims of sexual thoughts.